Assessment of venous hemodynamics and volume homeostasis during pregnancy: recommendations of the International Working Group on Maternal Hemodynamics. (6th June 2018) - Gyselaers, W.; Spaanderman, M.; ,
ABSTRACT: Venous hemodynamics and volume homeostasis are important aspects of cardiovascular physiology. However, today their relevance is still very much underappreciated. Their most important role is maintenance and control of venous return and, as such, cardiac output. A high‐flow/low‐resistance circulation, remaining constant under physiological circumstances, is mandatory for an uncomplicated course of pregnancy. In this article, characteristics of normal and abnormal venous and volume regulating functions are discussed with respect to normal and pathologic outcomes of pregnancy, and current (non‐invasive) methods to assess these functions are summarized. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.